An investigation into the efficacy of technical illustrations depicting physical orientation in sports procedures - Roy, Debopriyo (Cogent social sciences, 2017)
This study on mental imagery set out to investigate the efficacy of technical illustrations depicting physical orientation in sports procedures. The study was carried out by junior level students on an undergraduate degree in computer science at a Japanese technical university with no specialized knowledge of information design or visual communication. The study participants were asked to match body and overhead images shown from different height perspectives (waist and chest height) and camera positions (front, 1/3rd side, side, 1/3rd back, back) of a man holding a bat and a man hitting with a bat. These physical actions were selected by the researchers as they can typically be seen in multiple sports such as baseball, rounders or cricket, thus widening the potential applicability of the study findings. Overall, the study participants achieved relatively high levels of accuracy in matching the body and overhead images and no consistent or clear pattern emerged with regard to preferred height perspectives or camera positions. However, what can be suggested is that the study participants appeared to prefer - and the mean accuracy levels were higher for - viewpoints shown into the display plane. In addition, the study participants self-reported relatively high overall confidence in their matches despite not having any specialised knowledge of visual communication. It is hoped that this study and accompanying literature review could help technical communicators in thinking about how to design 2D technical illustrations and contribute to existing research into information design and visual communication, particularly in a sporting context.